The perceptions of private health insurance administrator senior managers about the National Health Insurance (NHI) in South Africa, Cape Town - Mxoli, Nonkqubela (Department of Public Health and Family Medicine, 2025)
South Africa is implementing a National Health Insurance system (NHI) as a funding mechanism towards attaining Universal Health Coverage (UHC). The main aim of the NHI is to protect citizens from financial hardships caused by out-of-pocket payments for accessing health services. In South Africa, a strong, robust private healthcare sector co-exists alongside the public health sector and consumes a disproportionate amount of healthcare; the healthcare sector co-exists the public health sector and consumes a disproportionate amount of healthcare resources it serves. It is essential, however, to understand the perspectives of all role-players in a complex health system, especially in times of significant policy change. This study focuses on garnering the perspectives of a somewhat ‘silent' group of actors in the private sector, namely administrators of medical schemes, a collective entity which manages a significant proportion of health care funds in the health care system. Study aim: This study explored the perspectives of senior managers in the health insurance administrator industry about the implementation of NHI in South Africa and their perceived role in it. This may contribute towards informing current policy initiatives underway to establish and implement an NHI system by adding perspectives of an otherwise unheard group. Methods: This study employed a qualitative study design to explore the perceptions of senior managers working in the Private Health Insurance Administrator (PHIA). First, relevant NHI-related policy documents were reviewed to identify the current policy stance on the role of medical schemes and PHIA within the NHI environment. This was followed by individual interviews with the senior managers, using a topic guide with pre-determined semi-structured questions. A purposive sampling technique was used to identify and select appropriate participants. Thematic analysis was used to identify key themes and subthemes, which informed the results and conclusions of the study. Results: The senior managers generally understood the proposed funding mechanism for the NHI and fully supported the move towards UHC. Similar to others, they highlighted concerns about the sustainability of the funding base if done through general taxes due to the small tax base. They also raised concerns about human resource shortages, particularly in the public sector, and corruption in the healthcare system, which threatens the sustainability of the NHI fund. Senior managers expressed uncertainties about their roles, which need to be clearly articulated in NHI policy documents. Software issues of trust, accountability, transparency, and social values were raised. However, senior managers felt that they had much expertise and practical tools to offer and expressed willingness to participate and contribute to the success of the NHI implementation. Conclusion: The results presented a gap in current policy about the future role of the PHIA/MSA industry in an NHI system and the value of exploring otherwise unheard voices within the context of the NHI implementation in South Africa. Moreover, senior managers in the PHIA industry are willing to contribute their experience and expertise to overall Universal Health Coverage (UHC) efforts.